Catfish growth using maggot supplementary feed in Sambas sub-district - Saifullah, Saifullah; Istiqamah, Nur; Sari, Ulia (Politeknik Negeri Sambas, 2024)
Feed is the largest aspect of cost expenditure in the operation of aquaculture activities. One commodity that is widely cultivated is catfish, which is easy to adapt, easy to maintain, and has a faster harvest time. The purpose of this study was to analyze the cost savings of catfish enlargement feed using supplementary Magot feed. Catfish enlargement business with a stocking amount of 3000 tails for Mr. Joko and 2000 tails for Mr. Munazi with a percentage of feed expenditure, namely 62% for Mr. Munazi and 55% for Mr. Joko. Both of them provide additional magot feed resulting in a profit of 1,075,000 IDR, for Mr. Munazi and for Mr. Joko of 2,040,000 IDR, with an R / C ratio value of Mr. Munazi 1.326 > 1 and Mr. Joko 1.463 > 1 so that their business is feasible to run. And can save costs for the procurement of pellets amounting to 1,260,000 IDR, and Mr. Joko 1,600,000 IDR or 38% for Mr. Munazi and 45% for Mr. Joko when compared to using 100% pellets.